Improving care quality with prison telemedicine: The effects of context and multiplicity on successful implementation and use. (July 2021) - Edge, Chantal; Black, Georgia; King, Emma; George, Julie; Patel, Shamir; Hayward, Andrew
Background: Prison telemedicine can improve the access, cost and quality of healthcare for prisoners, however adoption in prison systems worldwide has been variable despite these demonstrable benefits. This study examines anticipated and realised benefits, barriers and enablers for prison telemedicine, thereby providing evidence to improve the chances of successful implementation. Methods: A systematic search was conducted using a combination of medical subject headings and text word searches for prisons and telemedicine. Databases searched included: PubMed, Embase, CINAHL Plus, PsycINFO, Web of Science, Scopus and International Bibliography of the Social Sciences. Articles were included if they reported information regarding the use of/advocacy for telemedicine, for people residing within a secure correctional facility. A scoping summary and subsequent thematic qualitative analysis was undertaken on articles selected for inclusion in the review, to identify issues associated with successful implementation and use. Results: One thousand, eight hundred and eighty-two non-duplicate articles were returned, 225 were identified for full text review. A total of 163 articles were included in the final literature set. Important considerations for prison telemedicine implementation include: differences between anticipated and realised benefits and barriers, differing wants and needs of prison and community healthcare providers, the importance of top-down and bottom-up support and consideration of logistical and clinical compatibility. Conclusions: When implemented well, patients, prison and hospital staff are generally satisfied with telemedicine. Successful implementation requires careful consideration at outset of the partners to be engaged, the local context for implementation and the potential benefits that should be communicated to encourage participation.